1994
DOI: 10.1902/jop.1994.65.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Microbiological, and Histological Factors Which Influence the Success of Regenerative Periodontal Therapy

Abstract: The primary objectives of this double-blind, controlled clinical trial were to assess factor(s) which affect the success of guided tissue regeneration (GTR) procedures in mandibular Class II buccal furcation defects. Thirty subjects, with mandibular Class II furcation defects, were randomly assigned to one of two treatment groups; patients in Group A received oral hygiene instructions with scaling and root planing, while subjects in Group B received similar treatment but without subgingival scaling and root pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
1
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 26 publications
10
111
1
2
Order By: Relevance
“…The patient-related factors that have a negative influence on the regeneration of these lesions include smoking, stress, diabetes mellitus, acquired immunodeficiency syndrome and other acute and debilitating diseases, and the presence of multiple deep periodontal pockets. Age, gender and type of periodontal disease do not seem to play a major role in regenerative therapy (10,16).…”
Section: Patient Factors Influencing Successful Regenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…The patient-related factors that have a negative influence on the regeneration of these lesions include smoking, stress, diabetes mellitus, acquired immunodeficiency syndrome and other acute and debilitating diseases, and the presence of multiple deep periodontal pockets. Age, gender and type of periodontal disease do not seem to play a major role in regenerative therapy (10,16).…”
Section: Patient Factors Influencing Successful Regenerationmentioning
confidence: 99%
“…Bowers et al (10) demonstrated that despite comparable percentages of first and second molars with incomplete furcation closure, second molars exhibited a trend towards a higher proportion of defects with residual class II furcation. However, Machtei et al (16) showed that first and second molars responded similarly to regenerative treatment.…”
Section: Furcal Anatomymentioning
confidence: 99%
See 2 more Smart Citations
“…However, excessive accumulation of acidic degradation products has been reported which will leads to unwanted inflammatory reactions 5) . One main factor that contributes to unsuccessful tissue regeneration by GBR membrane treatment is the action of periodontal bacteria such as Porphyromonas gingivalis (P. gingivalis) and Actinobacillus actinomycetemcomitans 7) . The proliferation of these bacteria should be controlled on the site of GBR membrane restoration to ensure successful tissue migration, growth and proliferation 7) .…”
Section: Introductionmentioning
confidence: 99%